Digitale Telemedizin zur Überwachung chronischer Netzhauterkrankungen - ein klinisches Werkzeug für die Zukunft?: Übersichten - Terheyden, Jan H.; Mauschitz, Matthias; Wintergerst, Maximilian W. M.; Chang, Petrus; Herrmann, Philipp; Liegl, Raffael; Ach, Thomas; Finger, Robert P.; Holz, Frank G. (Die Ophthalmologie, 2024)
Background In view of the predicted increase in incidence and prevalence of chronic retinal diseases and undersupply of care in the population, telemedicine could contribute to reducing access barriers to healthcare and improving the results of treatment. Objective A literature review on remote monitoring of chronic retinal diseases was carried out. Material and methods The medical literature was searched for publications on remote monitoring of chronic retinal diseases. The results were compiled in a narrative overview. Results The four main topics in the literature are: validation studies, implementation strategies, acceptance/target group analyses and health economic analyses. Remote monitoring systems are based on visual function tests, imaging or patient reports and have been particularly investigated in age-related macular degeneration (AMD) and diabetic eye disease (DED). Studies indicate positive effects regarding an optimization of clinical care and a favorable safety profile but randomized controlled trials are lacking for the majority of monitoring tools. Conclusion Remote monitoring could complement existing care structures for patients with chronic retinal diseases, especially AMD and DED. Promising systems are based on hyperacuity or optical coherence tomography, while patient-reported data are not commonly used; however, there is currently insufficient evidence justifying the use of remote monitoring systems in chronic retinal diseases in Europe and more research on the validation of remote monitoring systems is needed.